The effects of asthma medications on reactive oxygen species production in human monocytes. (3rd April 2018) - Tsai, Ming-Kai; Lin, Yi-Ching; Huang, Ming-Yii; Lee, Min-Sheng; Kuo, Chang-Hung; Kuo, Po-Lin; Lin, Ching-Hsiung; Hung, Chih-Hsing
ABSTRACT: Objective : Asthma is a chronic inflammatory airway disease induced by many environmental factors. The inhalation of allergens and pollutants promotes the production of reactive oxygen species (ROS) leading to airway inflammation, hyper-responsiveness, and remodeling in allergic asthma. The effects of asthma medications on ROS production are unclear. The present study investigated the anti-ROS effects of current asthma medications including inhaled corticosteroid (ICS; budesonide and fluticasone), leukotriene receptor antagonist (LTRA; montelukast), long-acting β2 agonists (LABAs; salmeterol and formoterol), and a new extra-LABA (indacaterol). Methods : The human monocyte cell line THP-1 cells were pre-treated with different concentrations of the asthma medications at different time points after hydrogen peroxide (H2 O2 ) stimulation. H2 O2 production was measured with DCFH-DA by flow cytometry. Results : Montelukast, fluticasone, and salmeterol suppressed H2 O2 -induced ROS production. Indacaterol enhanced H2 O2 -induced ROS production. Budesonide and formoterol alone had no anti-ROS effects, but the combination of these two drugs significantly suppressed H2 O2 -induced ROS production. Conclusions : Different asthma medications have different anti-ROS effects on monocytes. The combination therapy with LABA and ICS seemed not to be the only choice for asthma control. Montelukast may also be a good supplemental treatment for the poorly controlled asthma because of its powerful anti-ROS effects. Our findings provide a novel therapeutic view in asthma.